2018
DOI: 10.1155/2018/1985784
|View full text |Cite|
|
Sign up to set email alerts
|

Origin of Boron and Brine Evolution in Saline Springs in the Nangqen Basin, Southern Tibetan Plateau

Abstract: The Nangqen Basin is a typical shearing-extensional basin situated in the hinterland of the Tibetan Plateau. It contains abundant saline spring resources and abnormal trace element enrichments. The hydrochemical molar ratios (Na/Cl, B/Cl, and Br/Cl), H-O isotopes, and B isotopes of the saline spring were systematically measured to describe the evolution of brines and the origin of the boron. The sodium chloride coefficient of the water samples in this area is around 1.0 or slightly greater, which is characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…11 B values of all samples are shown in tables 2 and 3 (Han et al 2018). The flow rates of the seven salt springs in this area are quite different, with the largest being 1.7 l/s and the smallest being 0.01 l/s.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…11 B values of all samples are shown in tables 2 and 3 (Han et al 2018). The flow rates of the seven salt springs in this area are quite different, with the largest being 1.7 l/s and the smallest being 0.01 l/s.…”
Section: Resultsmentioning
confidence: 91%
“…For d 11 B, the d 11 B-B relationships were analysed and the results showed that the leaching from the surrounding rocks (marine carbonate rocks and volcanic rocks) are the main sources of the B isotopes in the saline springs. It is speculated that the saline springs in the Nangqen basin were leached from the underground salt layer during atmospheric precipitation or groundwater upwelling and then formed on the exposed surface (Han et al 2018). Table 2.…”
Section: H O and B Isotopesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the article titled "Origin of Boron and Brine Evolution in Saline Springs in the Nangqen Basin, Southern Tibetan Plateau" [1], there was an error in the order of the second and third affiliations. Additionally, the Laboratory name in the second affiliation should be changed from "Key Laboratory of Salt Lake Geology and Environment of Qinghai Province" to "Qinghai Provincial Key Laboratory of Geology and Environment of Salt Lakes."…”
mentioning
confidence: 99%